Prinsip Keadilan Dan Kepastian Hukum Dalam Penentuan Tingkat Risiko Usaha Dan Pemberian Sanksi Administratif di Provinsi Lampung - Hardiansyah, Mas Achmad; Sumarja, FX; Ridlwan, Zulkarnain; Sunaryo, Sunaryo; Budiyono, Budiyono (Universitas Sang Bumi Ruwa Jurai, 2025)
Determining the level of business risk and imposing administrative sanctions are two important pillars in the regulatory framework for investment and business in Indonesia, including in Lampung Province. This policy, which is based on the Job Creation Law and its implementing regulations, aims to create a conducive business climate while ensuring compliance with legal norms. However, the implementation of this policy often faces crucial challenges in balancing the principles of justice and legal certainty. Justice demands that the treatment of business actors must be proportional, considering the capacity, intent, and impact of violations, and providing equal opportunities. Meanwhile, legal certainty requires clear, transparent, and predictable standards in the risk assessment and sanctioning process, so that business actors have a definite grip. This study aims to analyse in depth how the principles of justice and legal certainty are internalized and implemented in the regulations and practices of determining the level of business risk and imposing administrative sanctions in Lampung Province. The normative legal research method with a conceptual and legislative approach is used to examine relevant laws and regulations and policy documents. In addition, an empirical approach through interviews with relevant stakeholders (local governments, business actors, and academics) will enrich the analysis with a practical perspective. The results of the study are expected to identify potential disharmony between the two principles, formulate an ideal model for determining risk and imposing more balanced sanctions, and provide policy recommendations to improve the effectiveness and legitimacy of the regulatory system in Lampung Province, in order to support sustainable economic growth based on justice and the supremacy of law